Sequência didática para o ensino sobre a condução de calor - Costa, Hiram Jephson Gabriel da (2024)
The present study aims to investigate the development and implementation of a didactic sequence for teaching heat conduction, within the context of Physics teaching in Brazil. The central research question is: how can the implementation of a didactic sequence based on experiments impact the learning of heat conduction concepts? To answer this question, the study is based on Jerome Bruner's Discovery Learning Theory, which highlights the importance of students' prior knowledge in the assimilation of new concepts. The method adopted involves the creation of a didactic sequence that combines experimental activities, theoretical reflections and critical questions, aiming to actively engage students in the learning process. The research highlights the use of Problem-Based Learning (PBL) and other innovative methodologies, which place the student at the center of the learning process, promoting the development of cognitive and practical skills. The conclusions of the study indicate that the didactic sequence developed was effective in promoting a deeper understanding of concepts related to heat conduction. The results show that the integration between theory and practice, through experimental activities, reinforces students' prior knowledge and motivates the exploration and understanding of physical phenomena in a more meaningful way. Furthermore, the study suggests that this approach can be applied in other contexts of Physics teaching, contributing to improving the quality of teaching and learning in the area.